Social change in Southeast Asia - Schmidt, Johannes Dragsbaek; Hersh, Jacques; Fold, Niels (Addison Wesley, 1998)
Provides a comprehensive and in-depth examination of the ongoing process of development and societal transformation in a dynamic region of the Third World. Written by a team of specialists from the fields of development studies, sociology and political economy, the book looks at some of the fundamental problems facing South East Asia by addressing the following issues: the social constellations; class, culture and political legitimation; and industrialisation and labour regulation.